2022
DOI: 10.1101/2022.12.20.521248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socio-demographic determinants of monkeypox virus preventive behavior: a cross-sectional study in Pakistan

Abstract: Background: Monkeypox, a re-emerging zoonotic infectious disease, is striking the world with serious public health concerns, especially in non-endemic countries. The public's knowledge and attitude toward the monkeypox virus (MPXV) influence their adherence to preventive strategies. Therefore, we aimed to assess the general public's knowledge, attitudes, and perceptions (KAP) of MPXV in Pakistan. Methods: We collected data for this cross-sectional study from 1040 participants via an online self-reported questi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 57 publications
(72 reference statements)
1
7
1
Order By: Relevance
“…This contrasts to a study carried out by Hasham et al where findings revealed that of the total participants, 61.4% (n=639) were male, 61.8% (n=643) fall in age group 21–30years, 79.5% (n=827) were single. 79.5% (n=789) of the respondent residents of urban areas, and 57.2% (n= 595) achieved graduation level education [19]. This provides additional insights on the need for targeted public health and community engagement practices that are geographically specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts to a study carried out by Hasham et al where findings revealed that of the total participants, 61.4% (n=639) were male, 61.8% (n=643) fall in age group 21–30years, 79.5% (n=827) were single. 79.5% (n=789) of the respondent residents of urban areas, and 57.2% (n= 595) achieved graduation level education [19]. This provides additional insights on the need for targeted public health and community engagement practices that are geographically specific.…”
Section: Discussionmentioning
confidence: 99%
“…Infected persons must be supervised to stop the further spread of the virus to vulnerable populations. Previously, WHO and others have reported on the impacts of poverty on public health and infectious diseases, including mpox [8, 10, 19, 20]. Analyzing and understanding aspects of what protections are required and how they affect individuals and societies due to under investment in health system preparedness, lack of effective mpox vaccine and therapies, weaker health systems, limited research and response capacities, and how impoverishment reflects the difficult choices facing resource-limited African countries at greatest risk.…”
Section: Discussionmentioning
confidence: 99%
“…The reason could be thought that education plays an important part in helping people adopt healthier habits and tackling epidemics because it increases awareness of health-related issues. 37 Moreover, individuals with a higher level of education frequently have higher-paying jobs and have access to authoritative information from scientists and other experts. 60 Additionally, healthcare workers who fall under this category are more likely to study scientific research papers, engage in publications, participate in recent appropriate training and education programs, and improve their knowledge and skills through frequent reading.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Italy indicated that the knowledge status of Italian healthcare workers was quite unsatisfying, with substantial knowledge gaps towards mpox. 34 In a study conducted in Bangladesh, only 30.59%, 35 Indonesia, only 10%, 36 Pakistan, only 34.4%, 37 Turkey, 38 only 32.5%, Nigeria 39 only 37.8% of HCWs had good knowledge regarding the clinical presentation, transmission, and prevention of mpox. Similarly, a study in Lebanon reported low knowledge levels about mpox diagnosis and management among health workers where 33.7% of those surveyed had a good knowledge of mpox.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation